2021
DOI: 10.1001/jamadermatol.2020.4102
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Age, Period, and Birth Cohort Effects and Trends in Merkel Cell Carcinoma Incidence in the United States

Abstract: IMPORTANCE Merkel cell carcinoma is an aggressive, cutaneous, neuroendocrine cancer that is increasing in incidence. Understanding why the incidence of Merkel cell carcinoma is increasing through underlying factors, such as age effects, calendar period of diagnosis effects, and birth cohort effects, can help guide resource allocation and design of screening programs.OBJECTIVES To evaluate the associations of patient age, calendar period of diagnosis, and birth cohort with the increasing incidence of Merkel cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 29 publications
1
43
0
13
Order By: Relevance
“…9 While MCC is still a rare disease, its incidence continues to rise, and the United States has seen a 95% increase in the incidence from 0.5 cases per 100,000 in 2000 to 0.66 cases per 100,000 in 2016, with a predicted continued increase to 5130 cases/year by 2030. 3,10 Historically, treatment for MCC has been variable and included a combination of surgical resection of the primary with or without sentinel lymph node evaluation, radiation of the primary tumor and/or the associated lymph node basin, and chemotherapy, resulting in generally poor durable responses. 11 Recent clinical trials have demonstrated the efficacy of immunotherapy, while further defining the role of nodal staging and radiotherapy has led to improvements in treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…9 While MCC is still a rare disease, its incidence continues to rise, and the United States has seen a 95% increase in the incidence from 0.5 cases per 100,000 in 2000 to 0.66 cases per 100,000 in 2016, with a predicted continued increase to 5130 cases/year by 2030. 3,10 Historically, treatment for MCC has been variable and included a combination of surgical resection of the primary with or without sentinel lymph node evaluation, radiation of the primary tumor and/or the associated lymph node basin, and chemotherapy, resulting in generally poor durable responses. 11 Recent clinical trials have demonstrated the efficacy of immunotherapy, while further defining the role of nodal staging and radiotherapy has led to improvements in treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have identified and predicted an increasing incidence of MCC (Jacobs et al, 2021;Paulson et al, 2018;Stang et al, 2018;Zaar et al, 2016). Stang et al ( 2018) performed an analysis of MCC incidence across 20 countries and found increasing incidence in the majority of populations studied and stable incidence rates in some others (including Denmark and Norway).…”
Section: Detailed Answersmentioning
confidence: 99%
“…In another study of MCC incidence by Paulson et al (2018), an aging baby boomer generation was found to be driving the increasing number of new cases in the United States. In a longitudinal cohort study, Jacobs et al (2021) concluded that part of the increased incidence of MCC was due to increased detection. The increasing prevalence of immunosuppression may also be playing a role because it has been shown that MCC occurs more frequently in immunosuppressed individuals (Ma and Brewer, 2014).…”
Section: Detailed Answersmentioning
confidence: 99%
“…Though MCC cases are rare, the incidence of MCC has tripled over the last two decades and is projected to increase further in the future (Fitzgerald et al, 2015 ; Paulson et al, 2018a ; Stang et al, 2018 ; Freeman et al, 2019 ; Jacobs et al, 2020 ). MCC has a high rate of mortality with 5-year overall survival around 51% for patients presenting with local disease at the time of diagnosis, and worse prognoses for those with more advanced stages of disease (Harms K. L. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%